The immunomodulatory role of prednisone in patients with HIV-associated tuberculosis and assessment of its impact on lung function outcome - Stek, Cari (Department of Medicine, 2025)
In this thesis, I assess the effect of prednisone on immunopathology and pulmonary function in HIV-associated tuberculosis and tuberculosis-associated immune reconstitution inflammatory syndrome (TB-IRIS). I do this using data collected during the PredART trial. This randomized, double-blind, placebo-controlled trial showed that a 28-day course of prophylactic prednisone in adult patients identified as being at high risk for paradoxical TB-IRIS reduced the incidence of paradoxical TB-IRIS by 30%, without an excess of adverse events.